96 The Effect of Ramipril on the Rate of Aortic Dilatation in Bicuspid Aortic Valve Disease: Results from a Prospective, Double Blinded, Randomised Trial. (31st May 2014) - Loudon, Margaret; Bull, Sacha; Joseph, Jubin; Francis, Jane; Rider, Oliver; Karamitsos, Theodorus; Prendergast, Bernard; Neubauer, Stefan; Myerson, Saul
Abstract : Introduction: Dilation of the ascending aorta (AA) is associated with bicuspid aortic valve (BAV) disease and currently no medical therapy exists to delay or prevent AA dilatation in these patients. Inhibition of the renin–angiotensin system (RAS) appears toslow the rate of aortic dilatation in Marfan syndrome, but the effect on the aorta in BAV disease is unknown.We hypothesised that inhibition of the RAS in patients with BAV may reduce the rate of AA dilatation. Methods: This was a sub study of the RIAS trial (Ramipril In Aortic Stenosis), including only those subjects with BAV. RIAS was a randomised double blind, placebo controlled trial in which patients with moderate or severe aortic stenosis were randomised to ramipril 10 mg or placebo for one year. CMR scanning at 1.5 T was carried out at baseline and 12 months for assessment of aortic dimensions and valve morphology. Dimensions of the aorta were measured by a single observer (blinded to treatment allocation) at the aortic annulus, sinuses of Valsalva, sinotubular junction and mid-ascending aorta at the level of the pulmonary artery. Any change in dimensions from baseline in each group were noted and between group comparisons were made using dummy variable regression analysis. Results: 34 patients with BAV were recruited and completed the trial (18 ramipril, 16 placebo). (See Table 1 for patient characteristics). At 12 months, there were no significant differences from baseline in AA measurements in either group, nor between the ramipril and placebo groups (See Table 2). There was a consistent small increase in all dimensions in the placebo group compared to the ramipril group which was not statistically significant. Conclusions: Ramipril did not significantly alter the rate of progression of aortic dilatation at one year in this small study of patients with BAV. Our study was limited by a small number of patients and only one year follow up. Larger studies of RAS inhibition in this population with longer follow up may be warranted.